Globular Glial Tauopathy Type I Presenting as Atypical Progressive Aphasia, With Comorbid Limbic-Predominant Age-Related TDP-43 Encephalopathy - Rusina, Robert; Csefalvay, Zsolt; Kovacs, Gabor G.; Keller, Jiri; Javurkova, Alena; Matej, Radoslav (Frontiers in Aging Neuroscience, 2019)
Globular glial tauopathies (GGTs) have heterogeneous presentations with little available information regarding typical clinical manifestations. We report on a case of atypical primary progressive aphasia (PPA) due to comorbid GGT and limbic transactive response DNA binding protein of 43 kDa (TDP-43) proteinopathy. The initial clinical phenotype was compatible with the nonfluent-agrammatical variant of PPA and early hippocampal amnesia. Progressively, parkinsonism and supranuclear oculomotor impairment occurred, and finally, late mutism with frontal-type dementia, impaired comprehension, and behavioral manifestations developed. The neuropathology was characteristic of GGT type I with vascular changes and comorbid limbic-predominant age-related TDP-43 encephalopathy (LATE). Our findings expand the clinical spectrum of GGTs to include a complex progressive aphasia syndrome. The extraordinary feature, in this case, was the combination of two progressive aphasia subtypes, that is, the early nonfluent-agrammatical variant and the late semantic variant. Our findings also expand the spectrum of neuropathological comorbidities in GGT.